2020
DOI: 10.1055/s-0040-1709666
|View full text |Cite
|
Sign up to set email alerts
|

Is Group B Streptococcus Colonization Associated with Maternal Peripartum Infection in an Era of Routine Prophylaxis?

Abstract: Objective This study aimed to assess whether colonization with group B streptococcus (GBS) is associated with maternal peripartum infection in an era of routine prophylaxis. Study Design This study presented a secondary analysis of women delivering ≥37 weeks who underwent a trial of labor from the U.S. Consortium on Safe Labor (CSL) study. The exposure was maternal GBS colonization and the outcome was a diagnosis of chorioamnionitis, and secondarily, analyses were restricted to deliveries not admit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…One possible explanation is access to care, where those with private insurance may be more inclined to seek care and receive an antibiotic in the first place as well as subsequent care and documentation if they were to develop an allergy. Group B Streptococcus colonization was associated with decreased odds of SSI, consistent with the findings of other authors in the setting of routine prophylaxis [ 37 ]. Women with group B Streptococcus most likely received additional antibiotic therapy, particularly if they labored prior to their cesarean birth.…”
Section: Discussionsupporting
confidence: 90%
“…One possible explanation is access to care, where those with private insurance may be more inclined to seek care and receive an antibiotic in the first place as well as subsequent care and documentation if they were to develop an allergy. Group B Streptococcus colonization was associated with decreased odds of SSI, consistent with the findings of other authors in the setting of routine prophylaxis [ 37 ]. Women with group B Streptococcus most likely received additional antibiotic therapy, particularly if they labored prior to their cesarean birth.…”
Section: Discussionsupporting
confidence: 90%
“…With these interventions, recent studies have suggested that GBS colonization are associated with a lower odds of chorioamnionitis. 11 Additionally, obstetric comorbidities are also associated with an increase in antibiotic use during pregnancy, which may in turn decrease rates of neonatal infections. 104 While studies of invasive GBS infection in non-pregnant adults demonstrate increased incidence of infection, many of these studies do not independently investigate the incidence of GBS UTIs.…”
Section: Discussionmentioning
confidence: 99%
“…10 Following initiation of routine GBS screening and prophylaxis, maternal GBS colonization during pregnancy is now associated with lower odds of chorioamnionitis compared to prior to these interventions. 11 Over the past two decades, the epidemiology of invasive GBS infections in non-pregnant adults has evolved. A recent population-based surveillance study suggests a rising incidence of invasive GBS infection in non-pregnant adults, especially with increasing age.…”
mentioning
confidence: 99%
“…Furthermore, patients who were positive for Group B Strep status (GBS) were less likely to be admitted upon presentation to the ED. With appropriate screening and peripartum prophylaxis, the incidence of maternal infections is decreased [ 6 ]. Hence the antibiotics used to treat GBS may confer protection against infections.…”
Section: Discussionmentioning
confidence: 99%